Efficiency of Determination of Elemental Composition of Metals and their Topography in Objects of Biological Origin Using Spectrometers - Mikhailenko O.V.1 , Roshchin H.H.2 , Dyadik ?.?.2 , Irkin I.V.2 , Malisheva T.A.3 , Kostenko Ye.Ya.4 (Indian Journal of Forensic Medicine & Toxicology, 2021)
Bodily injuries, caused by firearms and special non-lethal means, which are provided for law enforcementagencies and special services and they are available to the civilian population as well (pistols for firingammunition equipped with elastic bullets, stun guns, etc.,) and the consequences of torture using variousmethods and the traumatic factors that caused by them have to get expert objective assessment. Among otherlaboratory studies, it is important to determine the characteristics of the composition of chemical elementsin objects of biological and non-biological origin by performing X-ray fluorescence spectral analysis usingmodern spectrometers. The object: to determine the characteristics of the elemental composition of metalsand their topography in injuries caused by gunshots and stun gun by conducting X-ray fluorescence spectralanalysis using spectrometers “ElvaX CEP-01” and “M4 TORNADO”. Conclusions: the use of spectrometersincreases the accuracy and objectivity of expert examinations of injuries caused by firearms and electricshock device as they have a wide range of chemical elements detection in the composition of the products ofthe shot and the electro tag from sodium to uranium. Using X-ray fluorescence spectral analysis, it is possiblenot only to detect metals in the layers of soot on injuries, but also to conduct a targeted “microscopic” studyof their topography for partial group identification of firearms and the installation of electrode metal, whichacted as a contact body conductor. X-ray fluorescence spectral analysis is a non-destructive research method.